Trend Analysis of West Bengal Universities (India) Based on NIRF Ranking - Rahaman, Jiaur; Das, Biswajit (Journal of Data Science, Informetrics, and Citation Studies)
The present study analyses the scientific productivity of University of Calcutta and Jadavpur University for the study period from 2002 to 2021 using the Web of Science database. The retrieved data has been analyzed on the following parameters; year-wise distribution of publication, authorship pattern, degree of collaboration, most productive authors, collaborative institution, and preferred source for publication. A total of 10856 and 14669 records from both universities have been retrieved. The results show that productivity has a fluctuating trend in the publication growth pattern in both universities. The study found that the author S Ghosh has published 653 articles; 7582 total citations and 42 h-index values are the top research productivity of C.U. research output. The study also found that S Das is the most prolific author J.U. with 957 articles, 22006 citations, and 65 h-index values.
Keywords: West Bengal’s University; Trend Analysis; Authorship Pattern; Prolific authors; VOSviewer; International Collaboration.